New H-ALPHA Emission Stars in A Region to the East of the T-Association Near Rho Ophiuci - Pik Sin The; Ham Keng Lim (Journal of Mathematical and Fundamental Sciences, 1964)
The result of a survey of H-alpha emission objects in an area of approximately 25 square degrees centered on the star CD -24°12765 (R.A.=16h38.m5; Dec.=-24°22';1950), is presented. Only 33% of H-alpha emission stars discovered by Dolidze and Arakelyan (1959) which are located in  the present survey region, are redetected in our plates. A total number of 32 new H-alpha emission objects are found. Their position and finding charts are given.